Revision of Anisepyris Kieffer (Hymenoptera, Bethylidae), with description of 135 new species - Barbosa, Diego N.; Azevedo, Celso O. (Zootaxa, 2018)
The identity of many species of Anisepyris Kieffer is currently unknown, mostly because the available taxonomic data are not sufficiently accurate to allow for precise identifications. To solve this problem, all 121 described species were investigated, including the analyses of 115 holotypes and 26 allotypes. Almost all Neotropical species of Epyrinae and many from the Nearctic were also examined in order to recognize possible species of Anisepyris misclassified in other genera. The ten species-groups included in Anisepyris are redefined. And the female genital structures of the genus are investigated for the first time. Based on this, we recognize 119 previously described species as belonging to Anisepyris, one species is transferred to Laelius Ashmead, L. foveaticeps (Rosmann & Azevedo) comb. nov., one is transferred to Chlorepyris Kieffer, C. nigerrimus (Evans) comb. nov., and 135 new species are described to science, so that the genus is now contains 254 species. They are recorded from 31 countries of the New World. Lectotypes are designated for A. aurichalceus (Westwood) and A. planiceps (Fabricius). The previously identified species-groups are re-organized into six, and seven additional species-groups are proposed are new. Identification keys for Anisepyris species-groups and species are provided.